Local community and visitor awareness of firefly conservation in Kuala Selangor, Malaysia - Roslan, Nadirah; Samdin, Zaiton; Wan Mohamad, Wan Norhidayah (Forestry Department Peninsular Malaysia, 2020)
Firefly is a unique beetle that produces light beneath its body. The synchronous light of firefly has a positive impact on the socio-economy of local community and acts as a tourism icon in Kuala Selangor. The present study analyses the awareness among visitors and local community of firefly conservation in Kampung Kuantan Firefly Park, Kuala Selangor. The study was conducted based on stratified sampling where face to face interview was performed on 730 respondents; where 400 were from the local community and 330 visitors. Results showed that the respondents were aware of the declining firefly population as a result of anthropogenic activities. The results also revealed that the respondents have a good awareness of firefly conservation as respondents showed in depth knowledge and understanding on the importance, disturbance and role of fireflies. Factor analysis served to determine the correlation between the variable by processing a set of similarity factor. Firefly conservation emerged as the main component of awareness, followed by specific knowledge and disturbance of the firefly ecosystem adding to the recent information on firefly conservation awareness among local community and visitors.